Orientalol L–P, novel sesquiterpenes from the rhizome of Alisma orientale (Sam.) Juzep and their nephrotoxicity on HK2 cells. (18th July 2018) - Zhang, Jianqing; Jin, Qinghao; Li, Shiyou; Wu, Jia; Wang, Zhen; Hou, Jinjun; Qu, Hua; Long, Huali; Wu, Wanying; Guo, Dean
Abstract : Two new sesquiterpenes and three new nor-sesquiterpenes from the rhizome of Alisma orientale (Sam.) Juzep, and their nephrotoxicities. Abstract : Two new sesquiterpenes (1–2 ) and three new nor-sesquiterpenes (3–5 ) were obtained from the rhizome of Alisma orientale (Sam.) Juzep, one of which (2 ) possessed an unprecedented cyclopentene and furanone containing natural skeleton. Their structures and relative stereochemistry were elucidated by NMR spectroscopy ( 1 H and 13 C NMR, HSQC, HMBC, NOESY) and electronic circular dichroism (ECD) and HR-ESI-MS data analyses. Two plausible biosynthetic pathways for compound1 and2 were discussed. The nephrotoxicities of these compounds were evaluated on normal human HK2 cells by high content screening, and neither the MeOH extract nor the compounds possessed potential nephrotoxicity in vitro .